«Gastroenterological» rheumatology: differential diagnosis of early arthritis - E. A. Galushko; A. M. Lila (Современная ревматология, 2019)
In real clinical practice, rheumatologists constantly face with the problem of differential diagnosis of rheumatic (RDs) and non-rheumatic diseases, as well as various RDs with similar symptoms. Most of the RDs are multisystemic and heterogeneous in clinical symptoms, course, and outcomes. Their clinical, laboratory, and instrumental signs that could be considered as the gold standard to confirm the diagnosis are not defined in all nosological entities. Therefore, the diagnostic process, especially in early arthritis caused by systemic inflammation, is complex cognitive in nature and requires the synthesis of many data that are usually not taken into account in a simple algorithm, the basis of which is a set of classification criteria.The review presents the issues of differential diagnosis of early arthritis in gastrointestinal tract diseases, such as celiac disease, microscopic colitis, PPP syndrome, etc.